An IoT-Integrated Framework for Real-Time Monitoring and Control of Renewable Energy in Smart Grids for Sustainable Network Computing - Souptik Sen (International Journal of Intelligent Systems and Applications in Engineering, 2020)
This paper outlines IoT-assimilated architecture for monitoring and control of renewable energy in smart grids which thereby strengthens the concept of sustainability in networked computing. Rising usage of renewable source of energies like solar or wind power generation needs efficient management to maintain stability, reliability and utility front in smart grids. The framework proposed in this paper uses IoT-based methodologies for integrating different energy sources within a sole architecture And those same capabilities allows acquiring information related to time-series data, the analysis of these and can be also implemented as a control method. Sensors networks are installed with the help of which energy generation and consumption is monitored, communication modules to send data as input through machine learning algorithms for implementing energy distribution in a streamlined manner from the master control system. Also, a dynamic load balance and prediction-based maintenance are provided to save the energy wastage and maintain the appliance working continuously. This in itself is critical because the system can respond and make decisions on-the-fly using future-state predictions of energy supply and demand, which improves grid resilience. The integration of IoT devices provides additional data accuracy to deliver specific metrics for grid performance and sustainability. The framework was validated by simulating in smart grid environment and showing significant improvements related to energy efficiency, cost effectiveness, and carbon footprint. The illustration of this study demonstrates the role IoT can play in revolutionizing renewable energy management within smart grids, fostering sustainable network computing techniques.